THE EFFECT OF REPEATED BEANS CROP ON GROWTH DEVELOPMENT AND GRAIN YIELD DEPENDING ON MINERAL FERTILIZER STANDARDS IRRIGATION UNDER CONDITIONS OF EROSIONED SOIL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article given the scientific sources on the achievement of high grain yields as a result of an increase in the number of pods when applying mineral fertilizer standards N50Ð 80Ðš60 kg /hec. for repeated mowing after autumn wheat in addition to good growth and development in the washed part of the soil under typical gray soils under erosion.